Оцінка якості та показники спермопродукції баранів-плідників різних порід - Миколайчук, Людмила Петрівна; Mykolaychuk, L. P.; Mykolajchuk, L. P.; Mykolaychuk, Lyudmyla Petrovna; Mykolaychuk, Ludmila; Mykolaichuk, L. P.; Mykolaichuk, Liudmyla; Похил, Володимир Іванович; Pokhil, Volodymyr; Pokhil, V.; Pokhil, V. I.; Pokhyl, V.; et al. (Дніпровський ДАЕУ, 2023)
Проведено дослідження показників спермопродукції баранів-плідників різних порід. Встановлено домінування гіссарських баранів за якісними показниками спермопродукції. A study of sperm production indicators of breeding rams of various breeds was conducted. The dominance of Hissar rams in terms of quality indicators of sperm production was established.
Evaluation of the quality and indicators of sperm production of different breeds of rams
Миколайчук Людмила Петрівна https://orcid.org/0000-0001-5331-719X Похил Володимир Іванович https://orcid.org/0000-0002-2994-879X
Keywords: концентрація; concentration; барани-плідники романівської та гіссарської порід; breeding rams of the Romanov and Hissar breeds; об’єм еякуляту; volume of ejaculate; рухливість; mobility